Kenya CAADP bienniel review brief: Africa agriculture scorecard performance and lessons - Okeyo, Isaac; Love, Josephine; Karugia, Joseph; Guthiga, Paul (International Food Policy Research Institute, 2019)
In 2003, Africa adopted the Comprehensive Africa Agriculture Development Programme (CAADP), an agriculture-led integrated development framework to boost African Agriculture. CAADP signatory states, including Kenya, committed to investing at least 10 percent of their budgets in the agricultural sector to attain a minimum 6 percent average annual growth in agricultural gross domestic product (AgGDP). By August 2017, 50 countries were engaged in CAADP, 42 had developed CAADP compacts, and 33 had National Agriculture Investment Plans (NAIPS) In June 2014 at the 23rd Assembly of the African Union (AU) Heads of State and Government in the capital of Equatorial Guinea, African leaders adopted the Malabo Declaration on Accelerated Agricultural Growth and Transformation for Shared Prosperity and Improved Livelihoods. The declaration reaffirmed the commitments of the 2003 Maputo Declaration and added new commitments, including ending hunger and halving poverty by 2025, tripling intra-African trade in agricultural commodities and services by 2025, enhancing resilience in livelihoods, and strengthening mutual accountability for actions and results.